Effectiveness of a Health Education Program on Coronary Artery Bypass Graft Patients’ Knowledge in Surgical Specialty Hospital-Cardiac Center in Erbil City - Dlzar Omer Qadir; Yousif Mohammed Younis (Erbil Journal of Nursing and Midwifery)
Background and objective: Coronary Artery Bypass Graft is considered an important surgical procedure, and due to the lack of sufficient knowledge in CABG patients, it is necessary and vital to carry out interventions to improve the knowledge of patients. Therefore, the purpose of this study is to determine the effect of a health education program on patients' knowledge.